Evaluation of Laboratory Risk Indicator for Necrotizing Fasciitis (LRINEC) Scoring System for Detecting Necrotizing Soft Tissues Infections in Patients with Diabetes - Zia, Shakeel Ahmed; Orfi, Fayyaz Ahmad; Khalid, Muhammad Umair; Rehman, Abdul; Ali, Waqas Farooq; Muhammad Shahzad (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the risk of necrotizing fasciitis using Laboratory Risk Indicator for Necrotizing Fasciitis scoring system. Study Design: Comparative prospective study. Place and Duration of Study: Department of General Surgery, Combined Military Hospital, Rawalpindi, Pakistan, from Jan to Aug 2022. Methodology: Using non-probability consecutive sampling technique, 278 participants were enrolled in the study. Among these patients with NF, 98 were cases and 180 were controls, having uncomplicated soft tissue infections (cellulitis or abscesses). A preliminary demographic profile, history of comorbidities, drug history, smoking history, or history of trauma within a week of enrolment at the inpatient facility was acquired. LRINEC Score was calculated with baseline C-reactive protein, white cell counts, sodium, creatinine, hemoglobin, and glucose. Results: Mean age of participants was 46.92±8.18 years where 208(74.8%) of the participants were males. LRINEC score ≥6 (cut off value) was computed among 78(79.6%) in confirmed cases of NF whereas only 13(7.2%) among controls. The sensitivity, speciﬁcity, positive predictive value, and negative predictive value were 79.6%, 92.7%, 85.7%, and 89.3% respectively. Conclusion: LRINEC scoring system in conjunction with clinical suspicion is a useful, reliable, and cost-effective scoring system that can help diagnose NF and distinguish it from other soft tissue infections.